Pengaruh Atribut Produk, Gaya Hidup, Dan Celebrity Endorser Terhadap Keputusan Pembelian Smartphone Di Kota Surakarta - Handayani, Lilis Tri; , Drs. Sri Padmantyo, M.B.A (2017)
This study aims to determine the effect of product attributes, lifestyle, and celebrity endorser towards purchace decision of smartphone in Surakarta. Sample of this study is smartphone users in Surakarta by distributing 150 questionnaires and 147 were returned. The results of this study indicate that product attributes and lifestyle have a significant influence on purchasing decisions, while celebrity endorser does not have significant influence towards purchasing decision. In addition, product attributes, lifestyle, and celebrity endorser simultaneously have a significant effect towards purchasing decisions ofsmartphone in Surakarta. The implication of this study is that the majority of smartphone users will be more consider the product attributes quality in deciding to buy a smartphone in order to support their lifestyle and activities.